2018
DOI: 10.1007/s00414-018-1936-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective resolution of the Y chromosome sublineages of the Iberian haplogroup R1b-DF27 with forensic purposes

Abstract: Single-nucleotide polymorphisms (SNPs) found within the non-recombining region of the Y chromosome (NRY) represent a powerful tool in forensic genetics for inferring the paternal ancestry of a vestige and complement the determination of biogeographical origin in combination with other markers like AIMs. In the present study, we introduce a panel of 15 Y-SNPs for a fine-resolution subtyping of the haplogroup R1b-DF27, in a single minisequencing reaction. This is the first minisequencing panel that allows a fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In total, 55 null alleles were observed at 14 different loci (DYS448, DYS390, DYS391, DYS456, DYS481, DYS460, DYS458, DYS449, DYS570, DYS576, DYS627, DYS518, and DYF387S1a/b). Furthermore, 71 micro-variants were found in 69 samples, including 8 single-copy loci, i.e., DYS518 ( (19,21), and DYS456 (15,16) were reported for the first time. All samples with variants are co-listed with their Y haplogroup affiliations in Table S2.…”
Section: Y-str Allele Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 55 null alleles were observed at 14 different loci (DYS448, DYS390, DYS391, DYS456, DYS481, DYS460, DYS458, DYS449, DYS570, DYS576, DYS627, DYS518, and DYF387S1a/b). Furthermore, 71 micro-variants were found in 69 samples, including 8 single-copy loci, i.e., DYS518 ( (19,21), and DYS456 (15,16) were reported for the first time. All samples with variants are co-listed with their Y haplogroup affiliations in Table S2.…”
Section: Y-str Allele Variantsmentioning
confidence: 99%
“…For forensic applications, population investigations by Y-STRs also generate much knowledge on inter-relationships among distinct male populations. In order to dissect the genetic structure of male populations, co-analysis of Y-STR and Y-SNP was conducted for diverse populations [10][11][12][13][14][15][16][17] but not for the majority of Chinese Han populations. In this research, preliminary comparative studies were conducted by genotyping commonly used Y-STRs and low-resolution Y-SNPs in two Chinese populations-Shandong Han and Yunnan Han-to characterize the patrilineal patterns in population genetics.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the Y-SNPs in the Flemish population identified the variant alleles in 270 male samples . Fifteen new SNPs were developed with the purpose of performing high resolution subtyping of the haplogroup R1b-DF27, which displays high frequencies in Iberian and Iberian-influenced populations …”
Section: Y-snps and X-snpsmentioning
confidence: 99%
“…125 Fifteen new SNPs were developed with the purpose of performing high resolution subtyping of the haplogroup R1b-DF27, which displays high frequencies in Iberian and Iberian-influenced populations. 126 Similarly, research studies on X-SNPs have been performed. Two different research groups applied the MALDI-TOF MS techniques to their samples in order to analyze a variety of X-SNPs in different populations.…”
Section: ■ Mixtures and Probabilistic Genotypingmentioning
confidence: 99%
“…This impact was even more pronounced in the Y chromosome, due to an almost complete genetic replacement of the diverse Copper Age lineages with R1b-M269 14 . One branch of this haplogroup, R1b-P312, is the most abundant in West Europe 13 and in turn, it splits into three main subbranches: U152, frequent in Northern Italy and the Alps regions 15 ; L21, more restricted to Ireland and the British Islands 16 ; and DF27, predominant in the Iberian Peninsula [17][18][19][20] . In this project, we focus on R1b-DF27, which has a high frequency in the Peninsula, reaching 40% of the Y-chromosome haplogroups both in Spain and Portugal, while it is much rarer elsewhere 21 .…”
mentioning
confidence: 99%